Current Trends in Wireless Technologies in Academic Libraries - Krishnamurthy, M.; Rajashekara, H.M. (DESIDOC Journal of Library & Information Technology, 2010)
Wireless communication is the transfer of information over a distance without the use of wires. Wireless communication is generally considered to be a branch of telecommunications. Wireless operations permit services, such as long-range communications that are impossible or impractical to implement using wires. Wireless communication brings fundamental changes to data networking and telecommunications, and makes integrated networks a reality. Wireless networks focus on networking and user aspects. Network architecture for personal communication systems, wireless LANs, radio, tactical and other wireless networks, and design and analysis of protocols are addressed on a regular basis. At present, the major application of Wi-Fi implementation in libraries is limited to information management. This paper elaborates the Wi-Fi in detail about the components, functions, area of applications, issues, and challenges. http://dx.doi.org/10.14429/djlit.31.1.763